2022
DOI: 10.3390/su14020829
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Assessing Performance of Mobile Broadband Networks and Future 5G Trends

Abstract: Mobile broadband (MBB) is one of the critical goals in fifth-generation (5G) networks due to rising data demand. MBB provides very high-speed internet access with seamless connections. Existing MBB, including third-generation (3G) and fourth-generation (4G) networks, also requires monitoring to ensure good network performance. Thus, performing analysis of existing MBB assists mobile network operators (MNOs) in further improving their MBB networks’ capabilities to meet user satisfaction. In this paper, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…e LSTM layer has a large number of series LSTM units, collectively referred to as the LSTM model [39][40][41]. ree multiplicative units are contained within the LSTM models: first, the input gate, which is used to store information from the current time; second, the output gate, which is responsible for displaying the results; third, the forget gate, which is used to select some already forgotten information from the past.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…e LSTM layer has a large number of series LSTM units, collectively referred to as the LSTM model [39][40][41]. ree multiplicative units are contained within the LSTM models: first, the input gate, which is used to store information from the current time; second, the output gate, which is responsible for displaying the results; third, the forget gate, which is used to select some already forgotten information from the past.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…In Figure 5, the X axis represents the number of nodes, and the Y axis represents the Average packet delay (s). The average packet delay of the techniques decreases as the number of sensor nodes increases, due to the ability to discover more qualifying nodes in their region to relay packets [46]. It is also found that the ECCAR has a longer average packet delay than the other methods.…”
mentioning
confidence: 89%
“…[60] presented research to map out the current state of knowledge on energy efficiency's impact on cloud computing and, in turn, help to build a better picture of the future of this area of study. No emphasis was given to techniques to reduce energy consumption [132][133][134][135][136][137][138][139][140][141][142][143][144][145].…”
Section: Related Surveysmentioning
confidence: 99%
“…In order to lower the carbon footprint of data centers, this research focused on decreasing brown energy and increasing renewable energy consumption. The authors [7] proposed a self-adaptive architecture based on microservices and renewable energy for interactive and batch workloads [140][141][142][143][144][145][146].…”
Section: Related Surveysmentioning
confidence: 99%
See 1 more Smart Citation